A new diapsid from the Middle Triassic of southern China. (26th April 2017) - Li, Chun; Fraser, Nicholas C.; Rieppel, Olivier; Zhao, Li-Jun; Wang, Li-Ting
Abstract: The Middle and early Late Triassic of southern China is well known for a remarkable diversity of marine vertebrates, particularly reptiles, including an abundance of intriguing new forms (e.g., Jiang et al., 2005 ; Hu et al., 2011; Li et al., 2016 ). Here we describe a new diapsid from Yunnan Province. It possesses an elongate neck that exhibits a remarkable similarity to that of many Protorosauria, yet in other respects the skull and postcranium are much less derived. The new taxon is part of the so-called Panxian-Luoping Fauna and the deposits correspond to the Upper Member of the Guanling Formation, comprising thin to medium bedded, gray to dark-gray laminated marly limestone and limestone, with several layers of bentonite intercalated in the fossil level at Panxian (Wan, 2002 ; Motani et al., 2008 ; Jiang et al., 2009 ). Their age is Pelsonian (middle Anisian, Middle Triassic) as is indicated by the conodont Nicoraella kockeli Zone (Sun et al., 2006 ; Zhang et al., 2009 ). A recent U-Pb study indicates the absolute age of these middle Anisian beds to be close to 244 Ma (Wang et al., 2014 ).